Everything will be fine. Memorable messages as a response to disclosing the experience of cancer - Mazurek, Emilia (Difficult situation in biographies: Volume 9, 2025)
Although cancer is no longer a taboo, and patients are shown expressions of concern and empathy, they still experience certain burdens and difficulties in social contacts. One of them is disclosing the disease. The decision to conceal or disclose the disease is a process that occurs over time and always entails certain consequences, such as confronting the reaction of people. Some messages formulated by people to whom the disease has been disclosed may be remembered for a long time and at the same time influence the values, behaviours and beliefs of patients. It makes them memorable messages. The cognitive aim of the study was to reconstruct the experiences of women with breast cancer related to communicating or not communicating to others about the cancer diagnosis and to reconstruct memorable messages that were a response to disclosing the disease. The practical aim of the study was to give a voice to women with breast cancer so that in the long term their experiences and reflections could be included in educational programs aimed at improving communication with a person with cancer and about cancer. A biographical study was conducted using an in-depth interview and lifeline. It involved 10 women aged 36 to 64. Five strategies of (non)disclosing cancer were distinguished: avoidance, concealment, selective disclosure, mediated disclosure and open disclosure. In response to the disclosure of the disease, the study participants received supportive, non-supportive and neutral memorable messages. The obtained results indicate the need for educational and counselling activities in the field of communication about cancer and with a person after the cancer diagnosis.